Image Color Enhancement Methods: An Experiment-Based Review - younis, zainab; Mohd Shafry Mohd Rahim; Farhan Bin Mohamed (School of Computing, Telkom University, 2024)
Image color enhancement is a vital aspect in the field of image processing. It is a technique to enhance and improve the image's visual quality. Color enhancement is applied in different applications such as photography, medicine, and computer vision. This research reviews eight methods-based color enhancement methods according to their methodology, complexity, pros, and cons. Then, three evaluation metrics used Colorfulness (CF), average saturation measure (ASM), and average chroma measure (ACM) to assess each method. The result showed that fuzzy enhancement (FE) exceeded other methods and scored the highest records. This study provides a beneficial resource for researchers involved in image enhancement, as it presents a complete review and detailed analysis of various academic studies published in reputable journals. The study evaluates each research work's findings, proposed algorithm, and accuracy using many assessment metrics. Furthermore, it emphasizes the strengths and limitations of each method, giving a performance analysis. Additionally, the study discusses future recommendations for improving the effectiveness of these algorithms. Finally, this research is a rich and reliable reference for scholars aiming to develop novel algorithms in this domain.